Development of a rapid co-prototyping environment for industrial services - Lammi, Miia Elina; Helo, Petri Tapani; Arrasvuori, Juha Henrik; Yli-Viitala, Pirjo Liisa; Pekkala, Janne; Peltonen, Sanna Liisa (University of Zagreb, Faculty of Mechanical Engineering and Naval Architecture, 2018)
Service-oriented industrial companies need to manage the complexity of developing new services (NSD) besides products. Prototyping offers a way to increase the success of NSD. There are service prototyping environments, but they fall short in effectiveness. CoProtolab concept was developed for effective, comprehensive, immersive and collaborative prototyping of industrial services in a physical and virtual environments. The research follows an axiomatic design theory and results in a theoretical model for studying and developing virtual, physical and social service prototyping environments.
Keywords: product-service systems (PSS); rapid prototyping; virtual prototyping; design science; fi=Tuotantotalous|en=Industrial Management|